Potentially stressful situations for nurses considering the condition of accreditation of hospitals - Higashi, Priscilla; Simonetti, Janete Pessuto; Carvalhaes, Maria Antonieta de Barros Leite; Spiri, Wilza Carla; Parada, Cristina Maria Garcia de Lima (Rev Rene, 2013)
Cross-sectional study that aimed to evaluate and compare the frequency of perceived/self-reported stress by nurses in hospitals with and without accreditation. One conducted in an accredited and two non-accredited hospitals in São Paulo in 2010 and 2011. Data collection included a questionnaire and the Stress Inventory for Nurses, with 262 participants, who evaluated stressful situations in the categories: Intrinsic Factors of Work, Interpersonal Relationships at Work and Stressful Roles in Career. The differences among hospitals concerning nurses’ perception/self-declaration about potentially stressful factors were evaluated by the chi-square test, considering p